PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS PELAYANAN SEKRETARIAT DPRD KABUPATEN GARUT - Rahmat Nugraha; Mulyaningsih; Gugun Geusan Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The effectiveness of public services is an important indicator in assessing the performance of public sector organizations, including regional legislative support institutions. The Secretariat of the Garut Regency DPRD plays a strategic role in supporting the smooth functioning of the DPRD through administrative, technical, and facilitative services provided to the leadership and members of the DPRD. Nevertheless, several challenges remain related to timeliness, responsiveness, and internal service coordination, which are presumed to be influenced by apparatus competence and organizational culture. This study aims to analyze the influence of apparatus competence and organizational culture on the effectiveness of public services at the Secretariat of the Garut Regency DPRD, both partially and simultaneously, as well as to identify differences in influence based on apparatus characteristics. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of the Secretariat of the Garut Regency DPRD. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the relationships among variables, as well as Multi-Group Analysis (MGA) to identify differences in influence based on demographic characteristics of the apparatus, particularly education level and age. The results show that apparatus competence has a positive and significant effect on the effectiveness of public services. Organizational culture is also proven to have a positive and significant effect on the effectiveness of public services. Simultaneously, apparatus competence and organizational culture make a strong contribution to public service effectiveness, with a coefficient of determination (R²) of 0.665, indicating that most of the variation in service effectiveness can be explained by these two variables. The results of the Multi-Group Analysis (MGA) indicate differences in the influence of apparatus competence and organizational culture based on education level, as well as differences in the influence of organizational culture across age groups, while the influence of competence remains relatively consistent across age groups. This study confirms that improving the effectiveness of public services at the Secretariat of the Garut Regency DPRD requires continuous development of apparatus competence and the strengthening of an adaptive, professional, and service-oriented organizational culture.